A Novel Local Autologous Bone Graft Donor Site After Scalp Tissue Expansion in Aplasia Cutis Congenita. Issue 4 (June 2016) - Hadad, Ivan; Meara, John G.; Rogers-Vizena, Carolyn R.
Abstract : Abstract: Aplasia cutis congenita (ACC) is a rare condition often presenting as an absent area of cutaneous scalp. The calvarium and dura may also be affected. Scalp reconstruction with tissue expansion is often needed for large defects. Patients involving deficient calvarial bone present a dilemma for the reconstructive surgeon, because bone graft donor sites are limited in young children. A thick, bony rim has been noted to form around the periphery of scalp tissue expanders. The authors present a series of 3 patients with ACC for whom this bony hyperostosis was used as donor particulate bone graft at the time of scalp tissue expansion. There was 85 to 100% graft ossification on postoperative computed tomography scan. There were no bone graft-related complications. In conclusion, the hyperostotic rim that forms after scalp tissue expansion can be successfully used as particulate bone graft, decreasing the number of procedures needed for patient with ACC and obviating the need for other donor sites.